NUTRITIONAL ASSESSMENT FOCUSING ON WOMEN AND CHILDREN IN PALAS VALLEY-KOHISTAN - Irshad, Romana; Khan, Ayesha; Mustafa, Adeela; Farooq, Umer (Journal of Ayub Medical College Abbottabad, 2018)
Background: Proper nutrition and health are fundamental rightsand nutrition is a cornerstone that affects and defines the health of all people, rich and poor. The study was done with the objectives to assess the people of Palas valley with regard to their nutritional status and dietary habits to devise ways and means to overcome primary and associated reasons for these problems. Methods: In this descriptive cross-sectional study residents of Palas valley of district Kohistan were included in the study through multistage cluster sampling method. The Palas valley was divided in to two: Kuz Palas (Lower Palas) and Bar Palas (Upper Palas). Two union council each from Kuz and Bar Palas were randomly selected Among the households, one adult male, one woman of childbearing age, one male child and one female child was selected randomly. Results: A total of 160 adult and children were interviewed and assessed for the nutritional status. Out of total of 80 children 61 (76.25%) had visible BCG scars. Among children 77.5% were either thinly built or had poor built. Among male adults 95% were of normal built. In adult females, 60% were either of thin built or poor built. Twenty-two percent of male children and 30% of female children were found underweight. Fourteen (35%) males and females have a BMI between 17.1-18.5 while only 6 (15%) of the females have BMI more than 18.5. Conclusion: Poverty and illiteracy in the absence of effective social and health services is playing havoc with the population of Palas valley. Poor sanitation and poor personal hygiene expose them to infections and parasitic diseases. Poor availability of food, lack of awareness and tough customs and traditions expose lead to malnutrition. Keywords: Nutrition; Nutritional assessment; Palas Valley; Kohistan